Asymptotic solution of the mathematical model of nonlinear oscillations of absolutely elastic inextensible weightless string - Krylovas, A.; Lavcel-Budko, O.; Miškinis, P. (Nonlinear Analysis: Modelling and Control, 2010)
The mathematical model of nonlinear oscillations of weightless string is analyzed. To find an asymptotic solution of the problem, uniformly valid in a long interval of time, an averaged system of integral differential equations has been constructed. A method for constructing special approximations of its solutions is proposed.
Keywords: perturbation methods; averaging; nonlinear waves; resonance; approximations